Comparative Story Drift Analysis of High Rise Building Structure between X-Braced Frame and Two Story X-Braced Frame - Fauzan Ahmad Sayed; Nugraha Bintang Wirawan; Ahmad Yudi (Journal of Science and Applicative Technology, 2019)
The high-rise building of steel structures requires strengthening system so that buildings are capable of carrying earthquake loads that may occur. Strengthening of steel structure building can be applied by providing stiffness of the structure in the form of mounting lateral stiffening system using eccentrically braced frame or concetrically braced frame. The purpose of this study is to analyze performance of story drift of the building structure in the form of horizontal drift values due to earthquake load on the building structure using the stiffening lateral x-braced frame and the two story x-braced frame. The research method using load of dynamic earthquake response spectrum analysis in accordance to SNI 03-1726-2012. The building models have 12 floors, located in Lampung city and was planned behave as an Intermediate Moment Resisting Steel Frame (IMRSF). Building model was designed and anlyzed using ETABS Version 9.7. This study shows story drift in type two story x-braced frame is smaller than the x-braced frame.